MEHANIČKE OSOBINE HELJDINE PERGE - Kubik, Lubomir (Journal on Processing and Energy in Agriculture, 2020)
Owing to a limited body of information on perga properties in the literature, the compressive properties of perga were determined in this study using uniaxial compressive tests. Certain mechanical properties such as the failure stress and strain and the modulus of elasticity can be used to evaluate the mechanical behavior of buckwheat (Fagopyrum esculentum) perga pellets under static loading. The Andilog Stentor 1000 testing machine (Andilog Technologies, Vitrolles, France) was employed for the uniaxial compression testing conducted. The perga samples considered were tested at different strain rates and loading speeds: four speeds ranging from 10 to 90 mm/min were used to achieve different strain rates. The influence of strain rates on the sample stress state was studied. The nonlinear regression model was tested to account for the stress-strain curves obtained. The loading curves of dependence of the stress on the strain were formed. Different strain rates and loading speeds were found to exert a significant effect on the stress and strain state of the perga samples examined, i.e. their overall firmness.
Keywords: čvrstoća, mehaničke osobine, veličina deformacije.